Raffles' Banded Langur : The Elusive Monkey of Singapore and Malaysia - Ang, Andie; Sabrina Jabbar (Singapore : World Scientific Publishing Co. Pte. Ltd., 2022)
c
Includes bibliographical references.
Keywords: Monkey -- Singapore; Monkey -- Malaysia; Monkey -- Conservation